Lack of evidence for tamoxifen- and toremifene-DNA adducts in lymphocytes of treated patients - Bartsch, Helmut; Nair, Jagadeesan; Grischke, Eva-Maria (Carcinogenesis, 2000)
Tamoxifen (TAM) is used for the adjuvant treatment of women with breast cancer and has also been recommended as a chemopreventive agent. Among unwanted side effects, TAM was shown to increase endometrial cancer in treated women by mechanisms that are not yet clearly understood. We studied DNA adducts in lymphocytes of female breast cancer patients treated with TAM or toremifene (TOR), a TAM analogue and compared them with adducts formed by TAM in rat liver, where the drug induces tumours. DNA adducts were measured by TLC-32P-post-labelling assays. After TLC, all DNA samples including DNA from untreated healthy women showed a faint radioactive zone, where the positive control DNA adducts isolated from the liver of rats treated with TAM migrated. The relative adduct levels were calculated from the radioactivity present in this zone. Means ± SD of adduct levels per 108 nucleotides (associated with this area) were for untreated volunteers (control) 1.83 ± 1.41 (n = 13), for TAM treatment 2.17 ± 3.04 (n = 25) and for TOR treatment 1.18 ± 1.05 (n = 8). Most of the human samples were further analysed by HPLC after labelling with 32P in order to compare adducts in human DNA with those in liver DNA isolated from TAM-treated rats. None of the human samples showed any peaks at retention times where putative TAM-DNA adducts were eluted. In conclusion, lymphocyte DNA from female patients treated at therapeutic levels did not show evidence of the formation of TAM- or TOR-DNA adducts.
Gesehen am 28.01.2021